Estrogens: a new player in spermatogenesis. - Christelle Delalande; Isabelle Galeraud-Denis; HĂŠlene Bouraima; Camille Bois; DorothĂŠe Silandre; Serge Carreau (Folia Histochemica et Cytobiologica, 2008)
The mammalian testis serves two main functions: production of spermatozoa and synthesis of steroids; among them, estrogens are the end products obtained from the irreversible transformation of androgens by aromatase. The aromatase is encoded by a single gene (cyp19) in humans which contains 18 exons, 9 of them being translated. In rat the aromatase activity is mainly located in Sertoli cells of immature animals and then in Leydig cells of adults. Moreover rat germ cells represent an additional source of estrogens: the amount of P450arom transcript is 3-fold higher in pachytene spermatocytes (PS) compared to gonocytes or round spermatids (RS); conversely, aromatase activity is more intense in haploid cells. Male germ cells of mice, bank vole, bear and monkey express also aromatase. In man besides Leydig cells, we have shown the presence of a biologically active aromatase and of estrogen receptors in ejaculated spermatozoa and in immature germ cells. Concerning aromatase, a 30% decrease of the amount of mRNA is observed in immotile compared to motile sperm fraction from the same sample; moreover the aromatase activity is also diminished of 34%. In asthenoteratozoospermic and teratozoospermic patients the aromatase gene expression is decreased by 67 and 52%, respectively when compared to normospermic controls. Statistical analyses between the sperm morphology and the aromatase/GAPDH ratio have revealed a high degree of correlation (r=-0.64) between the ratio and the percentage of abnormal spermatozoa (especially microcephaly and acrosmome malformations). Alterations of sperm number and motility have been described in men genetically deficient in aromatase, which together with our data, suggest a likely role for aromatase/estrogens in the acquisition of sperm motility. Therefore besides gonadotrophins and testosterone, estrogens produced locally should be considered as a physiologically relevant hormone involved in the regulation of spermatogenesis and spermiogenesis.